Evaluation of Green Efficiency of the Industrial Sector and Its Influencing Factors in West Sumatra - Ayu, Putri; Weriantoni, Weriantoni; Susanti, Oknovia; Putri, Meissytha; Kurnia, Rafiza (International Journal of Energy Economics and Policy, 2026)
One effort to achieve sustainable economic development is to conduct a green efficiency evaluation analysis. This study aims to evaluate green performance in the two-digit industrial sector in West Sumatra, as well as the factors that influence it. The purpose of this study is to evaluate green efficiency for 11 industries in West Sumatra and to analyze the impact of the energy structure, indirect taxes and COVID-19 on green efficiency in the industrial sector of West Sumatra. The methods used are SBM DEA and logistic panel regression. This policy simulation study will align with government policy to ensure that all research results comply with it. The results of the study indicate that in 2021 the efficient sectors were the food sector; the printing and reproduction of recorded media; chemicals and chemical materials; rubber and rubber materials; non-machinery metal goods and equipment; and the furniture sector. Meanwhile, the inefficient sectors were the beverage sector, the textile sector, apparel, paper and paper materials, and non-metallic minerals. When viewed from the influencing factors, indirect taxes had a significant positive impact on green efficiency in West Sumatra. Meanwhile, the energy structure and COVID-19 were not significant.